Reconstruction of The Application of Short Prison Sentence in the New Criminal Code - Hakim, Lukman (KRTHA BHAYANGKARA, 2025)
There has been a lot of criticism on the effectiveness of short imprisonment which has not been able to reduce the crime rate in a country, thus requiring other alternative solutions in overcoming this problem. In addition, there are studies that show that judges in Indonesia have a tendency to impose punishment decisions on criminal acts with minor criminal threats. For this reason, the New Criminal Code has reconstructed the application of short imprisonment by applying other alternative punishments such as fines and community service based on the objectives of punishment and guidelines for punishment, which in turn is expected to reduce the existing crime rate.